2020
DOI: 10.3390/ijms21145163
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potentials of Extracellular Vesicles for the Treatment of Diabetes and Diabetic Complications

Abstract: Extracellular vesicles (EVs), including exosomes and microvesicles, are nano-to-micrometer vesicles released from nearly all cellular types. EVs comprise a mixture of bioactive molecules (e.g., mRNAs, miRNAs, lipids, and proteins) that can be transported to the targeted cells/tissues via the blood or lymph circulation. Recently, EVs have received increased attention, owing to their emerging roles in cell-to-cell communication, or as biomarkers with the therapeutic potential to replace cell-based therapy. Diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 155 publications
(165 reference statements)
0
30
0
Order By: Relevance
“…Recent studies demonstrated that the benefits of MSC therapy could be due to their secretions, which play an important role in the regeneration of damaged tissues and may present considerable advantages over cell-based applications for manufacturing, handling and storage [29]. The possible therapeutic effect of MSCs in diabetic complications has also been suggested by the paracrine action of MSC-secreted factors (e.g., the secretome) as well as their capacity to generate insulin-producing cells [30] Moreover, the secretome is affected by the preconditioning of MSCs during isolation and maintenance [31,32] One paracrine mechanism of MSCs involves the secretion of extracellular vesicles (EVs), which are able to transfer various materials to recipient cells [33][34][35]. The present study showed that enhanced JAM2 expression and histophysiological alterations in lung tissue of diabetic mice were reduced via the paracrine action of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that the benefits of MSC therapy could be due to their secretions, which play an important role in the regeneration of damaged tissues and may present considerable advantages over cell-based applications for manufacturing, handling and storage [29]. The possible therapeutic effect of MSCs in diabetic complications has also been suggested by the paracrine action of MSC-secreted factors (e.g., the secretome) as well as their capacity to generate insulin-producing cells [30] Moreover, the secretome is affected by the preconditioning of MSCs during isolation and maintenance [31,32] One paracrine mechanism of MSCs involves the secretion of extracellular vesicles (EVs), which are able to transfer various materials to recipient cells [33][34][35]. The present study showed that enhanced JAM2 expression and histophysiological alterations in lung tissue of diabetic mice were reduced via the paracrine action of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…EVs have been used as carriers of therapeutic substances and the administration of exogenous EVs has great promise in diabetic treatment. The therapeutic potential of EVs in treating DM and its complications in animal trials have been summarized and discussed in recent reviews 432 , 454 . Here, we briefly discuss recent advances and the prospect of native EV-based therapeutics in DM and its complications.…”
Section: Clinical Applications Of Evs In Dm and Diabetic Complicationsmentioning
confidence: 99%
“…Apoptotic bodies are relatively large particles, with sizes ranging from 500 to 2,000 nm in diameter and derived from the late stage of apoptotic cells ( 19 , 20 ). Exosomes, the smallest vesicles, are derived from endosomal budding and released into the lumen through exocytosis ( 21 , 22 ). To explore the physiological and therapeutic functions of exosomes, the purification and quantification of exosomes are necessary to meet the requests of basic science and clinical practice.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%